STUDY OF COMBINING ABILITY AND GENE ACTION FOR YIELD AND YIELD COMPONENT CHARACTERS IN INTERSPECIFIC HYBRIDS OF COTTON (Gossypium hirsutum L. x Gossypium barbadense L.) - S. B. GOHIL; M. B. PARMAR; M. P. PATEL; D. A. PATEL (The Bioscan, 2020)
Present investigation was carried out to find out the combining ability of parents and identification of potential hybrids for improving seed cotton yield. To fulfil this objective, 42 interspecific hybrids were developed in line x tester analysis comprises of 7 lines of Gossypium hirsutum L. and 6 testers of Gossypium barbadense L. The variance ratio (σ2 gca/σ2 sca ) indicated the preponderance of non-additive genetic variance and greater magnitude of variance due to specific combining ability for all the characters except for days to 50 per cent flowering and plant height. Based on estimates of general combining ability effects four parents viz., AC 738, GN Cot. 22, GJC 101 and ARBB 1302 were found good general combiners for yield and its contributing traits suggesting exploitation of heterosis breeding for development of hybrids. The estimates of sca effects revealed that none of the hybrid was consistently significantly superior for all the traits. Only 13 hybrids had registered significant positive sca effects for seed cotton yield per plant. The best three hybrid combinations on the basis of significant and positive sca effects for seed cotton yield were GJHV 507 x GSB 43 (49.12), GJC 101 x CCB 40 (47.37) and GJC 101 x Suvin (43.63) and these crossed further evaluated for development of new hybrid.